THE COGNITIVE AND CULTURAL BENEFITS OF BILINGUALISM: INSIGHTS AND IMPLICATIONS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
The word “bilingualism” originates from the combination of two roots:“Bi”-two, “Lingua”-tongue or language. It illustrates that to be aware of knowing two languages, either by an individual speaker or by a community of speakers. Bilingualism literally revolutionises within an ambience where cultural exchange thrives, fostering deeper connections and enhancing cognitive flexibility. An important features of bilingualism are bilingual family and education. Because they provide with the foundational climates for acquiring and maintaining proficiency in two languages. Here’s why: in a bilingual family, children are often exposed to both languages from an early age, supposing them to learn each language in a natural and immersive way. In educational settings provide structured opportunities to learn both the academic and social aspects of a second language, enhancing fluency and literacy.